De transiciones democráticas a Momentos de Reconstrucción Constitucional: el caso de la Asamblea Constituyente 1978-1979 en Perú - Vidal Rodriguez, Nancy (2025)
Democratic transitions as a normative concept remain largely overlooked by constitutional theory. This article conceptualizes democratic transitions as ‘Moments of Constitutional Reconstruction’ in which the basic structure of the democratic regime is redefined according to the context. Three criteria allow us to recognize when these arrangements are foundational: (i) their common objective is to design lasting anti-authoritarian safeguards; (ii) the crisis involves broad social mobilization; and (iii) inter-party negotiation is pluralistic. Normatively, it is argued that modifying these foundational institutional arrangements requires reinforced standards of democratic legitimacy. As a case study, the Peruvian Constituent Assembly (1978-1979) is presented as the first Peruvian Moment of Constitutional Reconstruction, from which two foundational arrangements emerged. The first is the integration of the justice system within the balance of powers through the constitutionalization of the National Council of the Magistracy, the creation of the Constitutional Court, and the recognition of the jurisdiction of the Inter-American Commission and Court of Human Rights. The second arrangement is the strengthening of presidential power in the Executive-Legislative branch relationship. The Assembly incorporates a runoff election for the presidency, strengthens the Executive’s powers in economic and budgetary matters, and increases its legislative powers. Regarding the Legislative branch, it raises the standards for interpellation and censure, which are balanced by the president’s exceptional power to dissolve Congress. This set of institutions constitutes the basic conditions of Peruvian constitutional democracy. Therefore, its modification is not possible through ordinary legal channels. Overall, the article offers a normative theory of transitions as a foundational fundamental right and a comparative tool for distinguishing legitimate reforms from regressive redesigns that erode democracy, according to the context.